Perceptual Landscape of the Serbian Domestic Tourism Market - Teodorović, Milivoj; Popesku, Jovan; Pavlović, Danijel S. (Industrija, 2019)
The paper is a demographic analysis of the Serbian domestic tourism market based on the (n=302) survey responses. This paper aims to address the gap in the research literature that points to the perceptual state of domestic tourists in Serbia by conducting a perceptual demographic analysis based on gender, age, occupation and education. The research empirically proves the differences in the perception of domestic tourists about Serbia. The findings indicate mostly a positive image of Serbia as a tourist destination with higher marks given to gastronomy, entertainment, scenery, relaxing and casual atmosphere and hospitality. However, the observation shows that Serbia is not perceived as the first choice for vacation tourism by domestic tourists. Also, the study exposes that the level of education has the most differentiating impact on the perception of Serbia. A gap analysis was conducted using 23 perceptual variables categorized by awareness, quality, image and loyalty. The paper opens the door for further evaluation of the Serbian domestic tourism market and provides direction and the possible basis for the overall development of planning, investment, and marketing strategies.